MENINGKATKAN AKTIVITAS, KEMAMPUAN PEMECAHAN MASALAH, DAN HASIL BELAJAR MUATAN MATEMATIKA MENGGUNAKAN MODEL LEMPER PADA PESERTA DIDIK KELAS IV SD ISLAM SITI KHADIJAH - Rizky Amelia; Gusti Hidayati; Aslamiah; Celia Cinantya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This investigation examines the use of the LEMPER learning model in improving the activity, problem solving and mathematics learning outcomes of fourth grade students of SD Islam Siti Khadijah Banjarmasin. The LEMPER model combines problem-based learning, question-based stimulation and team game tournaments. Classroom action research (CAR) was conducted in this study for two learning cycles. The study population consisted of 23 fourth grade learners from Siti Khadijah Islamic Primary School in Banjarmasin. The results of this research found that teacher activity was ‘Very Good’ and learner activity increased rapidly to 87%. In addition, students' problem-solving skills also improved significantly, reaching 100%. Students obtained better learning outcomes overall in the affective, cognitive, and psychomotor aspects, increasing classically by 100%, 91%, and 100%.